SIGAP Home-Based Program to Foster Logical Thinking in Toddlers: A Case Study Approach - Evie Palenewen; Fachrul Rozie; Winda Karisma; Iman Nur Amain (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Developing logical thinking at an early age is a crucial foundation for children's cognitive growth. This study explores the implementation of the SIGAP Tanoto Foundation Home-Based Program in fostering logical thinking among children aged 2ÔÇô3 years, as well as the challenges encountered during its execution. Employing a qualitative case study approach, the research was conducted at RAS Nusa Indah in Sumber Sari Village. Data were collected through unstructured interviews, participant observation, and documentation. The findings reveal that the program was implemented in alignment with the learning modules, utilizing both existing and self-made educational tools. However, several challenges emerged, categorized as internalsuch as inconsistent attendance, incomplete materials, and children's physical and emotional conditionsand external, including facilitatorsÔÇÖ limited availability, poor road access, and low community engagement. The study underscores the potential of structured home-based programs to enhance early logical reasoning, while also highlighting the importance of addressing contextual barriers to optimize program delivery.┬á┬á